2017
DOI: 10.1002/lsm.22685
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor cisplatin nephrotoxicity in combined laser‐induced thermal therapy for cancer treatment

Abstract: This initial experience with (CDDP-LITT) indicates both safety and therapeutic potential for palliation of advanced head and neck cancer. However, safety and feasibility must be confirmed by longer follow-up and further escalation of CDDP doses in a Phase I study to determine maximum tolerated dose (MTD) and demonstrate tangible benefits for patients. Lasers Surg. Med. 49:756-762, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…34,35 Chemophototherapy has emerged as a promising treatment option for solid tumors. 18 Some studies have shown that a combination of DOX-based chemotherapy and ICG-based phototherapy can enhance antitumor efficacy and minimize systemic toxicity. [40][41][42][43] DOX is a broad-spectrum antitumor antibiotic that can inhibit the synthesis of RNA and DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 Chemophototherapy has emerged as a promising treatment option for solid tumors. 18 Some studies have shown that a combination of DOX-based chemotherapy and ICG-based phototherapy can enhance antitumor efficacy and minimize systemic toxicity. [40][41][42][43] DOX is a broad-spectrum antitumor antibiotic that can inhibit the synthesis of RNA and DNA.…”
Section: Discussionmentioning
confidence: 99%
“…5 The combination of chemotherapy and phototherapy has emerged as a promising strategy for cancer therapy, preclinically and clinically. 5,18 Concurrent introduction of chemotherapeutics can enhance the efficacy of phototherapy by further damaging tumor cells, preventing regrowth. Additionally, anticancer drugs themselves may generate oxidative stress, producing hydroxyl radicals which, when combined with PDT, may be sufficient to induce cell cycle arrest and subsequent cytotoxic death of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin is one of most commonly used chemotherapeutic drugs in the treatment of solid tumors including liver [1], lung [2], breast [3], cervical [4], ovarian [5], and testis [6] cancers. Although cisplatin has been shown to be one of the most effective anticancer drugs, its use in clinical application is limited because of its side effects in normal tissues [79]. The major consequences during cisplatin treatment are nephrotoxicity, ototoxicity, and neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that an alternative therapy should be considered for laryngeal SCC instead of additional PDT. Recently, some alternative or new therapies were reported that they showed noticeable differences in salvage treatment efficacy for head and neck cancers . They may be the alternative or salvage treatment before undertaking radical therapies.…”
Section: Discussionmentioning
confidence: 99%